Evaluating the influence of particle morphology and density on the viscosity and injectability of a novel long-acting local anesthetic suspension. (October 2022) - Wojtalewicz, Susan; Vizmeg, Jonathon; Erickson, Sierra; Lade, Caleb; Shea, Jill; Sant, Himanshu; Magda, Jules; Gale, Bruce; Agarwal, Jayant; Davis, Brett
Proper pain management is well understood to be one of the fundamental aspects of a healthy postoperative recovery in conjunction with mobility and nutrition. Approximately, 10% of patients prescribed opioids after surgery continue to use opioids in the long-term and as little as 10 days on opioids can result in addiction. In an effort to provide physicians with an alternative pain management technique, this work evaluates the material properties of a novel local anesthetic delivery system designed for controlled release of bupivacaine for 72 hours. The formulation utilizes solid-lipid microparticles that encapsulate the hydrophobic molecule bupivacaine in its free-base form. The lipid microparticles are suspended in a non-crosslinked hyaluronic acid hydrogel, which acts as the microparticle carrier. Two different particle manufacturing techniques, milling and hot homogenization, were evaluated in this work. The hot homogenized particles had a slower and more controlled release than the milled particles. Rheological techniques revealed that the suspension remains a viscoelastic fluid when loaded with either particle type up to 25% (w/v) particles densities. Furthermore, the shear thinning properties of the suspension media, hyaluronic acid hydrogel, were conserved when bupivacaine-loaded solid-lipid microparticles were loaded up to densities of 25% (w/v) particle loading. The force during injection was measured for suspension formulations with varying hyaluronic acid hydrogel concentrations, particle densities, particle types and particle sizes. The results indicate that the formulation viscosity is highly dependent on particle density, but hyaluronic acid hydrogel is required for lowering injection forces as well as minimizing clogging events.